(untitled) (Razão e Fé, 2026)
The aim of this article is to present the three stages of life conceived by the danish philosopher Søren Kierkegaard, respectively the Aesthetic Stage, the Ethical Stage and the Religious Stage. Considering that in Kierkegaard is the concrete individual who “assumes” these forms of existence, the first part of this work is a presentation of the individual in the kierkegaardian thought, who is inherently anguished. It is by the anguish that the individual can transition between the stages, doing what the author calls a leap. By seeking to escape anguish, and by not living an authentic life, the individual is affected by despair, the sickness unto death. In the second part of the study, differentiates the three stages. The Aesthetic Stage, characterized by the search of pleasure; the Ethical Stage, where although the individual is fitted into a “universal” standard, they have found the richness of being what they want to be; And finally, the Religious Stage, where a leap ad absurdum occurs to believe in the impossible. The work concludes showing that only the religious individual has the capacity to win the despair.